TIME FOR RADICAL CHANGE OF UNIVERSAL MYOCARDIAL INFARCTION DEFINITION HAS ARRIVED YESTERDAY - Yabluchanskiy, M. I.; Yabluchanskiy, A. M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
In this manuscript, we discuss a previously introduced definition of the myocardial infarction (MI), and propose to redefine it so it is not limited just to “a necrosis in the setting of myocardial ischemia”, which we think is the case only in the deceased individuals that died during the first few hours from the MI onset, but to include a broader description of the acute aseptic coronarogenic inflammation of the cardiac muscle. We suggest that the outcome of the MI to a large extant depends on the synchronization of the necrotic and reparative processes and that their desynchronization ultimately results in the development of MI complications. A better understanding of the MI and the use of appropriate definition is warranted for a development of new therapeutic targets.